Palpigradi (arachnida): morfologia, biogeografia e conservação - Souza, Maysa Fernanda Villela Rezende (2016)
The order Palpigradi is represented by small-sized arachnids that live in interstitial spaces of soil, under rocks, leaf litter and caves. This is the less studied order within Arachnida, and many biological, ecological and evolutionary aspects remain unknown. In this sense, the present study aimed to investigate morphological and biogeographical aspects of this order through the study of specimens deposited in biological collections and literature data. In the first manuscript, edaphic and troglobitic species were morphologically compared, and the troglobites presented more elongated appendages as well as more sensitive organs. Furthermore, the most important variables to discriminate these two groups were used to create a model to classify species with intermediate morphology as troglomorphic or edaphomorphic. In the second manuscript the occurrences of palpigrades in Brazil were compiled in order to identify areas of endemism. Then, biogeographical aspects of this group in Brazil were investigated, discussing the importance of caves and other areas that remained wet during previous climatic changes and of the sampling bias for the pointed areas of endemism. These two first manuscripts contribute to the better identification of troglomorphisms in palpigrades and show the distribution area of such species in Brazil, including areas with sinendemic troglobitic species. The information produced in these two manuscripts is essential for the preservation of species and their habitats, since according to the current Brazilian legislation, caves with at least one troglomorphic species cannot be target of irreversible impacts. In the third manuscript, the software MaxEnt was used to model environmentally adequate areas for the presence of edaphic palpigrades of the genus Eukoenenia in the world based on data of species occurrence and bioclimatic parameters (temperature, rainfall and altitude). Two models were constructed: in the first model, the occurrence records of species distributed in more than one continent (probably dispersed by anthropic actions) were not considered; in the second these points were included. Maps obtained for the two models show that regions with higher adequability are between the tropics and in the Mediterranean region. The occurrence points of widely distributed species coincided with areas considered environmentally adequate for the presence of other Eukoenenia species. Areas here identified as favorable to the occurrence of palpigrades might be considered priority for future field works that aim to obtain material for research on morphology, ecology and behavior, as well as for molecular researches. Simultaneously, these areas may be considered climatically propitious for the establishment of introduced species, thus highlighting the importance of a better control of invertebrates associated to the substrate of plants and a greater knowledge on biological interactions and habitat requirements of these arachnids.